Enzyme immunoassay compared with cell culture and immunofluorescence for detecting genital chlamydia. - Mumtaz, G (1989)
A novel enzyme immunoassay test (Pharmacia EIA) was evaluated against cell culture for the detection of chlamydial genital infection. Specimens were obtained from 525 patients (257 men and 268 women). Sensitivity, specificity, predictive value of positive (PVP) and predictive value of negative (PVN) for the new test were, respectively, 83.6, 98.5, 94.4 and 95.1% for men and 86, 97.2, 87.8 and 96.8% for women. Discrepancies were further evaluated by repeating the EIA, and by direct immunofluorescence on the EIA transport buffer. The sensitivity, specificity, PVP and PVN of the EIA against the combination of cell culture and direct immunofluorescence were, respectively 85.9, 100, 100, and 95.5% for men, and 90.5, 98.1, 92.3 and 97.7% for women. Overall agreement between the EIA and the combination of cell culture and direct immunofluorescence was 97%. The Pharmacia EIA is rapid and simple to perform and does not require elaborate equipment.